Hydration and cooling in elite athletes: relationship with performance, body mass loss and body temperatures during the Doha 2019 IAAF World Athletics Championships. Issue 23 (12th February 2021) - Racinais, Sebastien; Ihsan, Mohammed; Taylor, Lee; Cardinale, Marco; Adami, Paolo Emilio; Alonso, Juan Manuel; Bouscaren, Nicolas; Buitrago, Sebastian; Esh, Chris J; Gomez-Ezeiza, Josu; Garrandes, Frederic; Havenith, George; et al.
Abstract : Purpose: To characterise hydration, cooling, body mass loss, and core (Tcore ) and skin (Tsk ) temperatures during World Athletics Championships in hot-humid conditions. Methods: Marathon and race-walk (20 km and 50 km) athletes (n=83, 36 women) completed a pre-race questionnaire. Pre-race and post-race body weight (n=74), Tcore (n=56) and Tsk (n=49; thermography) were measured. Results: Most athletes (93%) had a pre-planned drinking strategy (electrolytes (83%), carbohydrates (81%)) while ice slurry was less common (11%; p<0.001). More men than women relied on electrolytes and carbohydrates (91%–93% vs 67%–72%, p≤0.029). Drinking strategies were based on personal experience (91%) rather than external sources (p<0.001). Most athletes (80%) planned pre-cooling (ice vests (53%), cold towels (45%), neck collars (21%) and ice slurry (21%)) and/or mid-cooling (93%; head/face dousing (65%) and cold water ingestion (52%)). Menthol usage was negligible (1%–2%). Pre-race Tcore was lower in athletes using ice vests (37.5°C±0.4°C vs 37.8°C±0.3°C, p=0.024). Tcore (pre-race 37.7°C±0.3°C, post-race 39.6°C±0.6°C) was independent of event, ranking or performance (p≥0.225). Pre-race Tsk was correlated with faster race completion (r=0.32, p=0.046) and was higher in non-finishers (did not finish (DNF); 33.8°C±0.9°C vs 32.6°C±1.4°C, p=0.017). Body mass loss was higher in men than women (−2.8±1.5% vs −1.3±1.6%, p<0.001), although not associated with performance. Conclusion: Most athletes' hydration strategies were pre-planned based on personal experience. Ice vests were the most adopted pre-cooling strategy and the only one minimising Tcore, suggesting that event organisers should be cognisant of logistics (ie, freezers). Dehydration was moderate and unrelated to performance. Pre-race Tsk was related to performance and DNF, suggesting that Tsk modulation should be incorporated into pre-race strategies.